The use of herders' accounts to map livestock activities across agropastoral landscapes in Semi-Arid Africa - Turner, M.D.; Hiernaux, Pierre H.Y. (Springer, 2002)
Improved understandings of the agricultural and range ecologies of semi-arid Africa require better information on the spatiotemporal distribution of domestic livestock across agropastoral landscapes. An empirical GIS-based approach was developed for estimating distributions of herded livestock across three agropastoral territories (around 100 km2 each) over a two-year period. Algorithms developed from regression analyses of herd tracking data (with R2s >= 0.67) are used to transform a more comprehensive but incomplete set of data generated from herders' accounts of their herds' grazing itineraries (400 herds following 6500 itineraries). The resulting characterization registers 40000 days of livestock activities across 694 land units (averaging 70 ha) over the study period. This study demonstrates that rural producers' knowledge of their daily extraction practices can be translated to fine-grained characterizations of extraction densities across mixed landscapes. The spatiotemporal distribution of livestock that is revealed by this approach diverges strongly from that predicted by commonly-used point-diffusion estimation procedures. Instead, the distribution reflects local patterns of land use, topography, vegetation, settlements, and water points. Grazing and nongrazing times spent in land units are not spatially correlated and the seasonality of grazing pressure is spatially variable. Therefore, the ecological impacts of livestock grazing are spatially variable at fine scales and there is a significant potential for livestock-mediated nutrient transfers across agropastoral landscapes. The georeferenced data produced by this approach not only will help evaluate the impact and sustainability of different management practices but also provides a strong empirical base for improved spatial modelling of herded livestock.